1996
DOI: 10.1139/g96-141
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinism of δ3-carene in maritime pine using RAPD markers

Abstract: An F2 progeny of maritime pine (Pinus pinaster Aïton) was used to investigate the mode of inheritance of δ3-carene using a quantitative and a qualitative approach. A previously reported genetic map constructed with random amplified polymorphic DNA (RAPD) markers made it possible to locate one major quantitative trait locus (QTL) accounting for most of the phenotypic variation of this trait on linkage group 5. In the qualitative approach, the "C" locus that controls the relative quantity of δ3-caren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…The most frequent results of inheritance studies suggested mono and oligogenic con trol of several monoterpenes in different coniferous species and more recently mo lecular studies have reported many plant genes that encode enzymes involved in the biosynthesis of terpenes (Nishizawa et al 1992, Plomion et al 1996, Raguso & Picher sky 1999, Shepherd et al 1999, Fischer et al 2001, Trapp & Croteau 2001, Fäldt et al 2003. Some seasonal changes have been confounded with epigenetic variations that occur in monoterpene proportion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent results of inheritance studies suggested mono and oligogenic con trol of several monoterpenes in different coniferous species and more recently mo lecular studies have reported many plant genes that encode enzymes involved in the biosynthesis of terpenes (Nishizawa et al 1992, Plomion et al 1996, Raguso & Picher sky 1999, Shepherd et al 1999, Fischer et al 2001, Trapp & Croteau 2001, Fäldt et al 2003. Some seasonal changes have been confounded with epigenetic variations that occur in monoterpene proportion.…”
Section: Discussionmentioning
confidence: 99%
“…Terpenes play a fundamental role in defence chemistry of the plant; terpenoid mixtures in conifer trees are constitutive (primary resin or pre-formed resin) and induced or newly synthesised in response to attack by herbi vores and microbes (secondary resin) (Lan genheim 1994, Raffa & Smalley 1995, Cates 1996. The relative proportions (percentages) of constitutive monoterpenes in mature tis sues are under strong genetic control and are little affected by environmental parameters (Baradat et al 1991, Hanover 1992, Plomion et al 1996. Therefore, monoterpenes have found applications in forest genetics as bio chemical markers in chemotaxonomy and in selecting less susceptible chemotypes to pests and diseases (Baradat et al 1991, Han over 1992, Michel ozzi 1999.…”
Section: Introductionmentioning
confidence: 99%
“…(Canard et al 1997). The results of Rafii et al (1996), Plomion et al (1996) and Trapp and Croteau (2001), although different, rehabilitate the tremendous amount of work aimed at studying the genetic control of terpenes. For several species in the genus Pinus it was defined that the β-pinene content is under genetic control of a single locus with two alleles (for P. sylvestris, Yazdani et al 1982Yazdani et al , 1985 for P. attenuata X radiata, Strauss and Critchfield 1982; for P. taeda Squillace et al 1980;for P. contorta, White 1983 andfor P. pinaster, Bernard-Dagan 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The relative proportions (percentages) of constitutive monoterpenes in mature tissues (which make up the constitutive monoterpene profile or the constitutive mixture) are strongly inherited, while the yeld ofmonoterpenes is subjected more to environmental parameters (Baradat eta/., 1991;Hanover, 1992;Plomion et a/., 1996). Correlations due to constraint are present when monoterpene proportions are used.…”
Section: Diterpenesmentioning
confidence: 99%